Rancang Bangun Aplikasi Portal Desa Kemang Tanduk Berbasis Website - Elis Puspita; Andi Christian; Rishi Suparianto (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
Kemang Tanduk Village, Rambang Kapak Tengah sub-district, Prabumulih City is one of the villages in the province of South Sumatra. One form of presentation of village information is through the delivery of information and public services. At present the village of Kemang tanduk, Rambang Kapak Tengah sub-district, Prabumulih city does not have the facilities to present information about the village so that the community has limited access to information about the village. The purpose of this final project is to build a system that can help village officials to present information and can make it easier for the public to access information by utilizing website-based technology. The research method used is descriptive qualitative method with data collection techniques in the form of observation, interviews, and literature study. The system development method uses the waterfall method, because the processes in this method are carried out sequentially. The system design tools used are use case diagrams, activity diagrams, and class diagrams. This application was built using a website with the PHP programming language and MySQL database.